PEMBERIAN LATIHAN ISOMETRIC QUADRICEPS TERHADAP PENURUNAN NYERI LUTUT PADA PENDERITA OSTEOARTHRITIS KNEE DEXTRA - Elsa Andrias Novembrian; Wahyuni Wahyuni; Restu Tama Febriany (Bajang Institute, 2022)
Introduction: Osteoarthritis of the knee is one of the conditions referred to as a cause of disability, especially in the elderly population. Knee OA is the most common articular disease in developed countries and is the leading cause of chronic disability, mostly from knee OA and hip OA cases. Quadriceps sisometric exercise is a form of strengthening exercise that is recommended to increase the strength of the quadriceps muscles and lower extremity muscles which are useful for supporting the body's burden so as to relieve the stress on the knee joint cartilage. Methods: This research uses a case study research method. Results: In this study, there was a decrease in pain at T1 to T6. At T1 it was silent pain 4 and at T6 it was 1, at T1 it was tenderness 6 and at T6 it was down to 1, at T1 it was tenderness 6 and at T6 it was 1, at T1 it was movement pain 6 and at T6 it was 1. Conclusion: Based on the description of the study and the discussion above that there was a significant reduction in pain in the treatment group that was given isometric quadriceps exercise for 4 weeks with a frequency of 2 times a week compared to the control group who was not given isomeric quadriceps exercise.